The Value of Institutions for Financial Markets : Evidence From Emerging Markets - Stratmann, Thomas (IMF Working Papers; Working Paper ;, 2009)
This paper investigates the value of political institutions for financial markets, using panel data from emerging market countries. We test the hypothesis that changes in political institutions, such as improvements in democratic rights and increased government accountability, have a direct effect on sovereign interest rate spreads. We find that financial markets value institutions over and above the economic and fiscal outcomes these institutions shape. Democracy and accountability generally lower sovereign spreads, political risk tends to increase them, and financial markets tend to view election years negatively.